2002
DOI: 10.1677/joe.0.1750605
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a negative feedback in the control of eel growth hormone by thyroid hormones

Abstract: The regulation of growth hormone (GH) by thyroid hormones (THs) has been shown to present species variation. We investigated the regulation of GH in the eel, a representative of an ancient group of teleosts. In vivo administration of triiodothyronine (T 3 ) or thyroxine (T 4 ) significantly reduced pituitary and serum GH levels, as measured by homologous RIA. In order to investigate the ability of THs to regulate GH production directly at the pituitary level, we used a long-term, serum-free primary culture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 50 publications
(47 reference statements)
0
13
0
Order By: Relevance
“…Eels were transferred to the laboratory and kept in running aerated freshwater (12 ± 2°C). Fish (8 eels/group) received one perivisceral injection per week of thyroxine (T4; Sigma, Saint Quentin Fallavier, France), estradiol (E2; Sigma) or testosterone (T; Sigma) (2 µg/body weight) suspended in saline (0.15 M NaCl) or of saline alone (controls) for 3 months, according to the protocol previously developed [31, 32]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eels were transferred to the laboratory and kept in running aerated freshwater (12 ± 2°C). Fish (8 eels/group) received one perivisceral injection per week of thyroxine (T4; Sigma, Saint Quentin Fallavier, France), estradiol (E2; Sigma) or testosterone (T; Sigma) (2 µg/body weight) suspended in saline (0.15 M NaCl) or of saline alone (controls) for 3 months, according to the protocol previously developed [31, 32]. …”
Section: Methodsmentioning
confidence: 99%
“…Individual pituitaries were extracted in 0.15 M NaCl by sonication (Bioblock Scientific, Illkirch, France), as previously described [32]. LH and GH levels were measured using respectively a radioimmunoassay (RIA) for carp LHβ subunit validated for European eel LHβ [34] and a homologous RIA for European eel GH [35].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in both glass and yellow eels, cortisol promotes gill and intestine Na + /K + -ATPase activity, i.e., adaptation to SW residency, probably in synergy with GH (Epstein et al 1971, Butler and Carmichael 1972, Wilson et al 2004). In addition, cortisol injections decrease plasma THs levels (Redding et al 1986), while THs exert a negative feedback on GH production by the pituitary, an eel-specific regulation (Rousseau et al 2002). These crossed negative feedbacks between THs vs. cortisol-GH could mediate the swap of glass eels from FW-oriented migration to settlement induced by a lowered body condition (Fig.…”
Section: Endocrine Factorsmentioning
confidence: 99%
“…In the European eel, it was demonstrated that GH was able to increase circulating T3 by stimulation of peripheral 5′-monodeiodination [104] and that both T3 and T4 could inhibit GH release and synthesis in vivo and in vitro [105]. In other teleosts, studies reported either stimulatory or no effects of TH on GH, and this species-related variation was also observed among mammals [for review, see [3]].…”
Section: Regulators Of Gh Involved In Energy Balancementioning
confidence: 99%